2015
DOI: 10.1177/0887403415586595
|View full text |Cite
|
Sign up to set email alerts
|

Set Up for Failure? Examining the Influence of Monetary Sanctions on Probation Success

Abstract: Recent critiques of the decision to make monetary sanctions a condition of probation have suggested that the practice could hinder the successful completion of probation. However, few studies have explored this relationship empirically, and among those that do, the findings are relatively inconclusive and often dependent on the sample and measures used. Building on this research, the current study examines the imposition of four monetary sanctions on a sample of felony cases involving indigent adult probatione… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
25
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 37 publications
0
25
0
Order By: Relevance
“…Two recent studies have been aimed at examining the link between all types of economic sanctions and recidivism. With a sample of 358 individuals whose cases were handled by a public defender's office in Florida, Iratzoqui and Metcalfe () found that the imposition of fees and restitution were unrelated to a probation violation. Legal factors (e.g., new charges, drug possession, and weapon possession), not fees or restitution, had the greatest impact on the recidivism of this undoubtedly impoverished group.…”
Section: Imposition and Payment Of Economic Sanctionsmentioning
confidence: 99%
“…Two recent studies have been aimed at examining the link between all types of economic sanctions and recidivism. With a sample of 358 individuals whose cases were handled by a public defender's office in Florida, Iratzoqui and Metcalfe () found that the imposition of fees and restitution were unrelated to a probation violation. Legal factors (e.g., new charges, drug possession, and weapon possession), not fees or restitution, had the greatest impact on the recidivism of this undoubtedly impoverished group.…”
Section: Imposition and Payment Of Economic Sanctionsmentioning
confidence: 99%
“…There has also been a parallel growth in the assessment of costs associated with correctional supervision (Pleggenkuhle, 2018;Ruhland, 2019;Ruhland et al, 2017). There is emerging evidence that suggests that monetary sanctions can complicate the reintegration process for individuals under correctional supervision (Harris et al, 2010;Pleggenkuhle, 2018) and can have negative effects on postconviction success (Heaton et al, 2017;Ruhland, 2019) including higher rates of recidivism (Iratzoqui & Metcalfe, 2017;Piquero & Jennings, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Compared with other economic sanctions, then, restitution holds the potential of positive outcomes for offenders, victims, and the community. The “specialness” of restitution has been recognized in that many researchers have tried to isolate information about restitution in their analyses as Barry Ruback, Lauren Knoth, Andrew Gladfelter, and Brendan Lantz did (: 789–813; see also Haynes, Cares, and Ruback, ; Iratzoqui and Metcalfe, ). Furthermore, calls to limit or eliminate the use of economic sanctions have been explicit that this does not apply to restitution (Beckett and Harris, ).…”
mentioning
confidence: 99%
“…Current knowledge regarding the imposition and payment of economic sanctions in general is mostly limited to a few states or to a few jurisdictions within those states (e.g., Alabama—Meredith and Morse, ; New Jersey—Weisburd et al., ; Louisiana—Henrichson et al., ; Pennsylvania—Ruback and Clark, ; Washington—Harris et al., ). Research aimed at examining recidivism is even more limited (e.g., Florida—Iratzoqui and Metcalfe, ; Pennsylvania—Ruback et al., ; and for juveniles—Haynes et al., , and Piquero and Jennings, ).…”
mentioning
confidence: 99%
See 1 more Smart Citation